The Effect of Multimedia Instructional Strategy In Enhancing The Students’ Academic Retention Ability: A Case Study Of Technical Colleges In Ondo State, Nigeria - Eze, Titus I.; Olumoko, B. O.; Obi, M. N.; Akingbemisilu, A. A. (Advances in Social Sciences Research Journal, 2020)
Academic retention ability of students for concepts taught in school has been of great concern to all stakeholders in education, especially as it is likely to have corresponding impact on both retention of students in high school grades, as well asin facilitating the capacity of educational institutions to retain the students in schools. These phenomena which constitute socio-economic problems worldwide apply also to students and educational situations in Nigeria. Thus these researchers set out to explore if a modern student-centred teaching method, like the multimedia instructional strategy could enhance students’ academic retention ability. In this study one research question guided the study and one hypothesis was tested at 0.05 alpha level of significance. The study adopted quasi-experimented design in which the pre-test, post-test, delayed post (Retention) design involved two unequal intact (experimental & control) groups. A total of 123 mechanical trade (year II) students from technical colleges in Ondo State, Nigeria, formed the population. By purposive sampling technique, the two intact groups of students (43 and 41) located in two local Governments Areas apart from each other, were selected to form a sample of 84. There were three data collection instruments namely the lesson plan for the control group, the lesson plan for the experimental group, and the Mechanical Trade Achievement Test (MTAT).These were validated by two mechanical technology lecturers from the Department of Technology and Vocational Education and one lecturer from Measurement Evaluation Unit, all from the Nnamdi Azikiwe University, Awka, Nigeria. Using the Kuder-Richardson formula 21 (KR-21) techniques, the MTAT was subjected to the reliability test to yield the reliability coefficient of 0.82. Thereafter, the experimental and the control groups were pre-tested, and then subjected to treatment (teaching) for five weeks and later post-tested. They were further tested (delay post test or retention test) after two weeks of no activity. The MTAT was used for all the tests, expect that each time, the content were reshuffled, and the colour of the paper changed. The resulting data were collected and analyzed with the mean for the research question and the analysis of the covariance (ANCOVA) at 0.05 level of significance. The findings of this study revealed that teaching with multimedia instructional strategy really enhanced student’s academic retention ability as shown from the mechanical trade students. It was therefore concluded that multimedia technology is more effective in improving students’ academic retention ability. Consequently it was recommended that teachers should adopt using multimedia technology in teaching.